First PCR isolation of Crithidia mellificae (Euglenozoa: Trypanosomatidae) in Apis mellifera (Hymenoptera: Apidae) in Italy - Cersini, Antonella; Antognetti, Valeria; Conti, Raffaella; Velletrani, Fabiana; Formato, Giovanni (Fragmenta entomologica, 2015)
Crithidia mellificae (Langridge & McGhee, 1967) is a trypanosomatid described in Apis mellifera (Linnaeus, 1758). The pathological effects of this parasite on the host are not well known. In this short communication, we report the first isolation of this pathogen in Italy, as realized in December 2013. The detection of Crithidia spp. was obtained by applying two PCR protocols that target the sequence of the mitochondrial cytochrome b (Cytb) and the sequence of small subunit ribosomal RNA (SSUrRNA), respectively. The PCR products were subjected to sequencing, which confirmed that the strain belonged to Crithidia mellificae.